Effects of novel C-methylated spermidine analogs on cell growth via hypusination of eukaryotic translation initiation factor 5A - Hyvönen, Mervi T. (2011)
The polyamines, putrescine, spermidine and spermine, are ubiquitous multifunctional cations essential for cellular proliferation. One specific function of spermidine in cell growth is its role as a butylamine donor for hypusine synthesis in the eukaryotic initiation factor 5A (eIF5A). Here, we report a novel series of mono-methylated spermidine analogs (α-MeSpd, β-MeSpd, γ-MeSpd, and ω-MeSpd) and their role in the hypusination of eIF5A and in supporting the growth of DFMO-treated DU145 cells. We also tested them as substrates and inhibitors for deoxyhypusine synthase (DHS) in vitro. Of these compounds, α-MeSpd, β-MeSpd, and γ-MeSpd (but not ω-MeSpd) were substrates for DHS in vitro, while they all inhibited the enzyme reaction. As racemic mixtures, only α-MeSpd and β-MeSpd supported long-term growth (9–18 days) of spermidine-depleted DU145 cells, whereas γ-MeSpd and ω-MeSpd did not. The S-enantiomer of α-MeSpd, which supported long-term growth, was a good substrate for DHS in vitro, whereas the R isomer was not. The long-term growth of DFMO-treated cells correlated with the hypusine-modification of eIF5A by intracellular methylated spermidine analogs. These results underscore the critical requirement for hypusine modification in mammalian cell proliferation and provide new insights into the specificity of the deoxyhypusine synthase reaction.